Collins cobuild illustrated intermediate dictionary of english (Glasgow, Great Britain Harpercollins publisher, 2012)
More than 55 new words have been added to the Collins cobuild illustrated intermediate dictionary of english, the new visual thesaurus helps learners develop fluency by providing alternatives to the 50 most over-used words in english
2 21
Keywords: English language -- Dictionaries